Awareness of Antimicrobial Stewardship Interventions Within a Community Hospital Network. (October 2020) - Hou, Cindy; Vyas, Nikunj; Kraemer, Marianne; Condoluci, David
Abstract : Background: A system of 3 community hospitals in New Jersey has actively engaged in antimicrobial stewardship since November 2014. Consultations with infectious diseases specialists are mandatory for patients with sepsis, severe sepsis, septic shock, patients on 3 or more antibiotics, and for those diagnosed with Clostridioides difficile infection (CDI). A multidisciplinary team meets monthly and has begun to improve the appropriateness of antibiotics use and to reduce antibiotic days of therapy per 1, 000 patient days. Recently, we participated in a targeted assessment program (TAP) for CDI, and we identified areas of opportunity for antimicrobial stewardship. Methods: The TAP survey was emailed to a wide distribution of employees in the hospital, primarily nurses, physicians, and others with a variable range of experience and for those working in the intensive care units and on the wards. Ultimately, the numbers of responses were 60 in hospital A, 88 in hospital B, and 124 in hospital C. Results: In hospital A, most respondents were nurses or nurse assistants or technicians (63%), and most of the total individuals surveyed worked outside the intensive care unit setting. In hospital B, nurses or nurse assistants or technicians comprised 69% of all responses. Hospital C had the highest percentage of physicians who responded (31%). One theme for all hospitals was that a little more than half of those surveyed felt that for patients with new or recent CDI infections, antibiotics prescribed for infections were reviewed by clinicians. Less than half of respondents believed that education was being given to patients and families about the risks of CDI from antibiotics. With regard to high-risk CDI antibiotics, there was a general lack of knowledge that these were being monitored. For example, survey respondents felt that this was always monitored on clindamycin by only 33% of respondents in hospital A, 40% in hospital B, and 42% in hospital C. With regard to strategies to reduce the unnecessary use of fluoroquinolones, the response of "always" ranged from 35% to 47% of the time. Conclusions: Even though hospitals may have robust antimicrobial stewardship programs, it is important to survey frontline staff. Although all of the antimicrobial stewardship interventions, such as monitoring high-risk-CDI antibiotics, reducing high-risk CDI antibiotics, among others, are performed, there may be lack of knowledge that these initiatives are even being implemented. In this TAP against CDI, we found opportunities to share data with respondents to increase awareness of antimicrobial stewardship to further combat hospital-acquired infections. Funding: None Disclosures: None